Sterile and dual-porous aerogels scaffolds obtained through a multistep supercritical CO2-based approach - Santos-Rosales, Víctor (2019)
Aerogels from natural polymers are endowed with attractive textural and biological properties for biomedical applications due to their high open mesoporosity, low density, and reduced toxicity. Nevertheless, the lack of macroporosity in the aerogel structure and of a sterilization method suitable for these materials restrict their use for regenerative medicine purposes and prompt the research on getting ready-to-implant dual (macro + meso)porous aerogels. In this work, zein, a family of proteins present in materials for tissue engineering, was evaluated as a sacrificial porogen to obtain macroporous starch aerogels. This approach was particularly advantageous since it could be integrated in the conventional aerogel processing method without extra leaching steps. Physicochemical, morphological, and mechanical characterization were performed to study the effect of porogen zein at various proportions (0:1, 1:2, and 1:1 zein: starch weight ratio) on the properties of the obtained starch-based aerogels. From a forward-looking perspective for its clinical application, a supercritical CO2 sterilization treatment was implemented for these aerogels. The sterilization efficacy and the influence of the treatment on the aerogel final properties were evaluated mainly in terms of absence of microbial growth, cytocompatibility, as well as physicochemical, structural, and mechanical modifications.